Turbo Code Design and Implementation of High-Speed Parallel Decoder - Yi Bo-nian (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Due to the high complexity Turbo decoding algorithm, implemented the hardware decoder logic of consumes more resources and storage resources, decode delay larger. In order to meet LTE systems, high reliable transmission of high data rate needs high speed Turbo decoder design faces enormous challenges. This topics select based on LTE system of parallel Turbo Code decoders hardware design and achieved as research direction, select FPGA(Virtex-6) as hardware design and achieved of platform, from Log-MAP algorithm of Sentinel of, and State measure value handed owned calculation in the of owned a of processing, and Diego generation decoding algorithm of parallel of, and parallel interwoven Manager design, and key path optimization technology, aspects analysis, design achieved has LTE Turbo Code high-speed parallel decoders. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2393